Cytoplasmic and nuclear Sw‐5b NLR act both independently and synergistically to confer full host defense against tospovirus infection. Issue 6 (18th July 2021) - Chen, Hongyu; Qian, Xin; Chen, Xiaojiao; Yang, Tongqing; Feng, Mingfeng; Chen, Jing; Cheng, Ruixiang; Hong, Hao; Zheng, Ying; Mei, Yuzhen; Shen, Danyu; Xu, Yi; et al.
Summary: Plant intracellular nucleotide‐binding leucine‐rich repeat (NLR) receptors play critical roles in mediating host immunity to pathogen attack. We use tomato Sw‐5b::tospovirus as a model system to study the specific role of the compartmentalized plant NLR in dictating host defenses against the virus at different infection steps. We demonstrated here that tomato NLR Sw‐5b distributes to the cytoplasm and nucleus, respectively, to play different roles in inducing host resistances against tomato spotted wilt orthotospovirus (TSWV) infection. The cytoplasmic‐enriched Sw‐5b induces a strong cell death response to inhibit TSWV replication. This host response is, however, insufficient to block viral intercellular and long‐distance movement. The nuclear‐enriched Sw‐5b triggers a host defense that weakly inhibits viral replication but strongly impedes virus intercellular and systemic movement. Furthermore, the cytoplasmic and nuclear Sw‐5b act synergistically to dictate a full host defense of TSWV infection. We further demonstrated that the extended N‐terminal Solanaceae domain (SD) of Sw‐5b plays critical roles in cytoplasm/nucleus partitioning. Sw‐5b NLR controls its cytoplasm localization. Strikingly, the SD but not coil‐coil domain is crucial for Sw‐5b receptor to import into the nucleus to trigger the immunity. The SD was found to interact with importins. Silencing both importin α and β expression disrupted Sw‐5b nucleus import and host immunity against TSWV systemic infection. Collectively, our findings suggest that Sw‐5b bifurcates disease resistances by cytoplasm/nucleus partitioning to block different infection steps of TSWV. The findings also identified a new regulatory role of extra domain of a plant NLR in mediating host innate immunity.